Menyusu Dini Dan Senam Nifas Terhadap Tinggi Fundus Uteri Ibu Postpartum Multipara - Fitriani Widyastanti; Elisa Elisa; Wagiyo Wagiyo (JURNAL KEPERAWATAN MERSI, 2019)
The hemorrhage of multiparous postpartum mothers occurs because the uterus has stretched so the uteri involution is slow. The lack of myometrial contraction cause a slow uteri involution so the decreasing of uteri fundus level is slow. The early breastfeeding and postpartum exercise are the ways that can be used to accelerate the decreasing of high fundus uteri. This research aims to know the influence of early breastfeeding and postpartum exercise to decrease the high fundus uteri of multiparous postpartum mothers at Klinik Utama Rawat Inap Ngesti Widodo Ungaran. The research method used is Quasi Experiment with post test-only non equivalent control group design. The number of samples are 30 respondents divided into control and intervention groups. The sampling technique used is total sampling. The data analysis used is Independent T-Test and obtained the result of p-value = 0.000 with α = 5% (0,05) showed that there is significant decreasing of high fundus uteri between early breastfeeding group than the combination of early breastfeeding and postpartum exercise. The average of high fundus uteri in the early breastfeeding group is 7,909 cm and postpartum exercise group is 4,820 cm. The conclusion, that combination of early breastfeeding and postpartum exercise affect the high fundus uteri.